2021
DOI: 10.3390/app11052278
|View full text |Cite
|
Sign up to set email alerts
|

Application of Life Cycle Assessment in the Environmental Study of Sustainable Ceramic Bricks Made with ‘alperujo’ (Olive Pomace)

Abstract: Investigations on the application of Life Cycle Assessment (LCA) to the construction sector have shown that the environmental impact of construction products can be significantly reduced. To achieve this, the use of best available techniques and eco-innovation in production plants must be promoted. In this way, the use of finite natural resources can be replaced by waste generated in other production processes, preferably available locally, stimulating the creation of more sustainable products. Conducting a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The findings revealed that this technology achieved a 35.74% reduction in greenhouse gas emissions and a 14.83% reduction in mineral resource consumption compared to traditional ceramic tiles. LópezGarcí a A et al [8] conducted an LCA-based comparative analysis between traditional ceramic tiles and tiles with 3%, 7%, and 10% olive residue additions. The results demonstrated that the incorporation of olive residue led to a reduction of over 8% in ecological toxicity, human toxicity, and eutrophication potential at the raw material stage compared to traditional ceramic tiles.…”
Section: Raw Materials Substitution Technologymentioning
confidence: 99%
“…The findings revealed that this technology achieved a 35.74% reduction in greenhouse gas emissions and a 14.83% reduction in mineral resource consumption compared to traditional ceramic tiles. LópezGarcí a A et al [8] conducted an LCA-based comparative analysis between traditional ceramic tiles and tiles with 3%, 7%, and 10% olive residue additions. The results demonstrated that the incorporation of olive residue led to a reduction of over 8% in ecological toxicity, human toxicity, and eutrophication potential at the raw material stage compared to traditional ceramic tiles.…”
Section: Raw Materials Substitution Technologymentioning
confidence: 99%
“…The possible incorporation of olive pomace into clay bodies for developing ecofriendly ceramic materials has been positively assessed [75,80], although results from a Life Cycle Assessment (LCA) indicate that associated environmental benefits are very limited [77]. Biomass bottom ash deriving from the combustion of olive cake or olive pomace together with almond shell can act as alkaline activator to develop chamotte-based geopolymers as substitutes for ceramic bricks [81].…”
Section: Olive Mill Waste Reused As Component In the Manufacture Of Sustainable Building Materialsmentioning
confidence: 99%
“…The aim of this study is to demonstrate the environmental benefit that can be achieved through the recycling of waste into construction materials using an objective tool, LCA. Although LCA is increasingly being used to analyze the life cycle of construction materials [40][41][42], there are few articles published to date that carry out a comparative study as presented in this work [43,44].…”
Section: Introductionmentioning
confidence: 99%